Peripheral neurological assessment methods for workers exposed to hand-arm vibration. An appraisal. - Haines, T.; Chong, J. P. (Scandinavian Journal of Work, Environment & Health, 1987)
Peripheral neurological assessment methods for workers exposed to hand-arm vibration have included vibration perception and esthesiometric threshold testing, electroneurography, handgrip force, and manipulative dexterity. For epidemiologic investigations with the purpose of detecting vibration effects anticipated as moderate to large in size in occupational populations, these methods have demonstrated their usefulness. Concerning their value in the assessment of individual workers, there is little quantitative information, as there have been no studies which have conducted rigorous "gold standard" neurological evaluation with which the results of independently performed diagnostic tests can be compared. However, results from four papers which used depth-sense (or ridge) and two-point discrimination esthesiometry were available for an analysis of the sensitivity of these tests in the detection of Taylor-Pelmear stages 2 and 3 of the hand-arm vibration syndrome. With specificity set at 90%, sensitivity ranged from 45 to 96% for depth-sense esthesiometry and from 19 to 75% for two-point discrimination. In addition, likelihood ratios were determined, as a measure of the capacity of the tests to alter pretest probability of disease. Because of their direct clinical interpretation and application, the use of likelihood ratios is suggested for future research on diagnostic methods used for vibration-exposed workers.